The Concept of Reggio Emilia Education in Early Childhood Education Learning in the Early 21st Century - Muslim Muslim; Tobroni Tobroni; Joko Widodo; Saiful Anwar (JIE (Journal of Islamic Education), 2025)
This study aims to analyze the implementation of the Reggio Emilia educational concept in early childhood learning at PAUD Aisyiyah in Bima City within the context of early 21st-century education. The Reggio Emilia approach emphasizes children as active learners who construct knowledge through exploration, collaboration, creativity, and interaction with their environment. This research employed a descriptive qualitative method to gain a comprehensive understanding of how the approach is applied in classroom practices. Data were collected through classroom observations, semi-structured interviews with teachers and school administrators, and analysis of relevant learning documents and teaching materials. The findings indicate that implementing the Reggio Emilia approach positively influences children's learning experiences and developmental outcomes. Children become more actively involved in learning activities, demonstrate higher curiosity, and participate more collaboratively with peers and teachers. Approximately 75% of the observed children showed improved social interaction and cooperation during group activities, while around 80% displayed greater enthusiasm and interest in participating in learning tasks. In addition, classroom environments designed to support exploration, such as learning centers, visual documentation, and project-based activities, were found to stimulate children's creativity and problem-solving skills. However, several challenges were identified during implementation. These include limited teacher training in the Reggio Emilia philosophy, limited learning resources, and insufficient parental involvement in supporting children's exploratory learning at home.